PEMANFAATAN LAHAN PEKARANGANN KOSONG MENJADI LAHAN PRODUKTIF DISAAT PANDEMI - Choeruli , Deni; Intan Hapsari , Galuh; Ahsin Mabrur , Muhammad; Trimerani, Resna (COVIT (Community Service of Tambusai), 2022)
The Covid pandemic has hampered activities in various countries, one of which is Indonesia. The pandemic has become a scourge in various sectors, especially agriculture. The thing that is most feared if this condition continues is the occurrence of a food crisis. So we need to rack our brains so that family food is maintained, namely by utilizing the yard. with the more productive use of yard land so that the community has a high level of food security. With this, the community will also have a source of family income, if the results obtained by utilizing the yard exceed the amount needed by the family. Depok village, Kandeman sub-district, Batang district is one of the villages targeted for the yard use program, where in this area there are still many yards that have not been used productively. The method used is socialization about the use of yard land, how to sow seeds and plant chili and eggplant with polybag media. The socialization was conveyed to the mothers who had done data collection as many as 20 people. During the socialization activity, the community seemed enthusiastic in listening to the material, asking questions, and those present exceeded the total number of data collected. The Covid pandemic has hampered activities in various countries, one of which is Indonesia. The pandemic has become a scourge in various sectors, especially agriculture. The thing that is most feared if this condition continues is the occurrence of a food crisis. So we need to rack our brains so that family food is maintained, namely by utilizing the yard. with the more productive use of yard land so that the community has a high level of food security. With this, the community will also have a source of family income, if the results obtained by utilizing the yard exceed the amount needed by the family. Depok village, Kandeman sub-district, Batang district is one of the villages targeted for the yard use program, where in this area there are still many yards that have not been used productively. The method used is socialization about the use of yard land, how to sow seeds and plant chili and eggplant with polybag media. The socialization was conveyed to the mothers who had done data collection as many as 20 people. During the socialization activity, the community seemed enthusiastic in listening to the material, asking questions, and those present exceeded the total number of data collected. Keywords: Pandemic, Outreach, Community Empowerment, Counseling